Successful percutaneous coronary intervention for multiple coronary artery aneurysms causing acute inferior myocardial infarction - Tsuyoshi Honda (Termedia Publishing House, 2021)
A 59-year-old man was referred to our hospital for chest pain he had been experiencing for several hours. The electrocardiogram showed ST-segment elevation in leads II, III, aVF, V4-V6. Emergent coronary angiography (CAG) showed a total occlusion of the proximal right coronary artery (RCA) with multiple calcified coronary artery aneurysms (CAAs) (Figure 1 A). There was no significant lesion of the left coronary artery.